Factor Substitution and Durability of Capital in a Two-Sector Putty-Clay Model - Adachi, Hideyuki (Econometrica, 1974)
[This paper investigates various properties of a two-sector putty-clay model in which physical durability of capital as well as its economic lifetime is a choice variable. Our model adopts Wicksell-Åkerman's hypothesis that the production of capital goods of greater durability can be accomplished only by incurring greater costs per unit of capital produced. Thus it is a synthesis of Wicksell's durability and putty-clay models. The case in which all capital goods are infinitely durable and are scrapped solely by obsolescence (i.e., pure obsolescence case) will appear as a special case of our model.]